Prevalence of Campylobacter spp. in retailed ready-to-eat sushi - Tan, Y. F.; Haresh, Kumar Kantilal; Chai, Lay Ching; Mohamad Ghazali, Farinazleen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
The prevalence of Campylobacter spp. in retailed sushi were examined using the techniques of polymerase chain reaction (PCR) in combination with most probable number (MPN) to quantify the bacteria in 150 samples obtained from three supermarkets. The average prevalence of Campylobacter spp. in retailed sushi was 26.6% with 32%, 16% and 32% from supermarket I, II and III, respectively. Campylobacter jejuni was found to be the predominant species in retailed sushi with 82.49% of all Campylobacter spp. positive samples. Campylobacter coli was not detected in all samples. The maximum MPN number of Campylobacter spp. in retailed sushi purchased from supermarket I, II and III ranged from 3.6-11.0 MPN/g, 9.4->1100 MPN/g and 27-1100 MPN/g, respectively. The isolation of C. jejuni from a variety of ready-to-eat retail sushi may indicate that these products can act as possible vehicles for the dissemination of food-borne campylobacteriosis.